2012
DOI: 10.1063/1.4740248
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit coupled potential energy surfaces and properties using effective relativistic coupling by asymptotic representation

Abstract: A new method has been reported recently [H. Ndome, R. Welsch, and W. Eisfeld, J. Chem. Phys. 136, 034103 (2012)] that allows the efficient generation of fully coupled potential energy surfaces (PESs) including derivative and spin-orbit (SO) coupling. The method is based on the diabatic asymptotic representation of the molecular fine structure states and an effective relativistic coupling operator and therefore is called effective relativistic coupling by asymptotic representation (ERCAR). The resulting diabati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…All-atom Monte Carlo simulations were performed using the ABSINTH implicit solvent model and forcefield paradigm as made available in version 2.0 CAMPARI simulation package ( ) ( Vitalis and Pappu, 2009a , b ; Radhakrishnan et al , 2012 ). Simulations were based on the abs_3.2_opls.prm parameter set in conjunction with optimized parameters for neutralizing and excess Na + and Cl – ions ( Mao and Pappu, 2012 ). Simulations were performed using a spherical droplet with a diameter of 285 Ã… with explicit ions to mimic a concentration of 10 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…All-atom Monte Carlo simulations were performed using the ABSINTH implicit solvent model and forcefield paradigm as made available in version 2.0 CAMPARI simulation package ( ) ( Vitalis and Pappu, 2009a , b ; Radhakrishnan et al , 2012 ). Simulations were based on the abs_3.2_opls.prm parameter set in conjunction with optimized parameters for neutralizing and excess Na + and Cl – ions ( Mao and Pappu, 2012 ). Simulations were performed using a spherical droplet with a diameter of 285 Ã… with explicit ions to mimic a concentration of 10 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…48,49 The spin-orbit interaction can couple states of different symmetries and spins; there is an intricate interplay between SOC and the JT (and pJT) effects. [50][51][52][53][54][55][56][57][58][59][60][61][62] The SOC operator should hence be included in the vibronic Hamiltonian expansion for those systems. Very recently, Domcke et al 38 derived the relations between the SOC matrix elements and the electrostatic Hamiltonian elements for p orbitals.…”
Section: Expansion Of Spin-orbit Matrix Elements In the P-type (E mentioning
confidence: 99%
“…[52][53][54] The interplay between SOC and JT/pJT effects has been a long lasting research subject. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] For JT/pJT systems with heavy nuclei, it is necessary to include the spin-orbit interaction in the vibronic Hamiltonian expansion. Very recently, Domcke et al 71 showed that there is a neat connection between the SOC and the electrostatic Hamiltonian matrix elements for a set of p Gaussian orbitals.…”
Section: Expansion Of Spin-orbit Matrix Elements In the Ptype Tetrahementioning
confidence: 99%